The expression of microRNA 574-3p as a predictor of postoperative outcome in patients with esophageal squamous cell carcinoma. Issue 1 (December 2016) - Okumura, Tomoyuki; Kojima, Hirohumi; Miwa, Takeshi; Sekine, Shinichi; Hashimoto, Isaya; Hojo, Shozo; Nagata, Takuya; Shimada, Yutaka
Abstract Background Despite advances in radical esophagectomies and adjuvant therapy, the postoperative prognosis in esophageal squamous cell carcinoma (ESCC) patients remains poor. The aim of this study was to identify a molecular signature to predict postoperative favorable outcomes in patients with ESCC. Methods As a training data set, total RNA was extracted from formalin-fixed paraffin-embedded samples of surgically removed specimens from 19 ESCC patients who underwent curative esophagectomy. The expression of microRNA (miRNA) was detected using a miRNA oligo chip on which 885 genes were mounted. As a validation data set, we obtained frozen samples of surgically resected tumors from 12 independent ESCC patients and the expression of miR-574-3p was detected by quantitative real-time PCR. Results Our microarray analysis in the training set patients identified three miRNAs (miR-574-3p, miR-106b, and miR-1303) and five miRNAs (miR-1203, miR-1909, miR-204, miR-371-3p, miR-886-3p) which were differentially expressed between the patients with (n = 14) and without (n = 5) postoperative tumor relapse (p < 0.01 andp < 0.05, respectively). Higher expression of miR-574-3p, which showed the most significant association with non-relapse (p = 0.001), was associated with favorable overall survival (p = 0.016). Real-time PCR experiments on the validation set patients confirmed that higher expression of miR-574-3p was associated with non-tumor relapse (p = 0.029) and better overall survival (p = 0.004). Conclusions Our results suggest that the aberrant expression of the miRNAs identified in this study plays key roles in the progression of ESCC. miR-574-3p was suggested to have a tumor suppressor effect, and thus, to be a predictor of postoperative outcome in patients with ESCC.